PENGARUH METODE PENAKSIRAN GADAI EMAS TERHADAP PENGAMBILAN KEPUTUSAN NASABAH BANK SYARIAH INDONESIA KC SURABAYA DARMO - Siti Khoiriyah; Khusnul Fikriyah (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2022)
Recovery after the COVID-19 pandemic is one of the factors in the decline in people's purchasing power. Where the policy of termination of employment for employees makes the community unproductive and has no income. To overcome this, people need alternative solutions that are fast and appropriate to get money in order to meet their needs. Gold pawning institutions become an alternative that is considered appropriate because with public investment in the form of gold and jewelry, they can be pawned to use their value. Bank Syariah Indonesia is a banking institution that has several superior products, one of which is the Gold Pawn which runs its operations based on sharia. This study uses quantitative research methods with a causal associative approach aimed at knowing and analyzing the causal relationship between two or more variables. The results of this study indicate the gold pawning method of BSI KC Surabaya Darmo and its influence on customer decision making. The appraisal practice is in accordance with sharia theory because the terms and conditions have been met. From this study it can be concluded that there is an influence between the assessment method on customer decision making.